2017
DOI: 10.1227/neu.0000000000001377
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Embolization Device for Small Intracranial Aneurysms: Evaluation of Safety and Efficacy in a Multicenter Cohort

Abstract: In the largest series on PED for small aneurysms to date, data suggest that treatment with the flow-diverting PED is safe and efficacious, with complication rates comparable to those for traditional endovascular techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 31 publications
2
39
0
1
Order By: Relevance
“…Important to note is that the rates of complications seen after PED placement (16%), coiling (9%), and clipping (17%) are comparable to those reported from previous studies. 17,21,26 Other studies have found similar selection bias as a result of the evolving usage of PEDs. 26 Other trends in our cohort could be sources of confounding.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Important to note is that the rates of complications seen after PED placement (16%), coiling (9%), and clipping (17%) are comparable to those reported from previous studies. 17,21,26 Other studies have found similar selection bias as a result of the evolving usage of PEDs. 26 Other trends in our cohort could be sources of confounding.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies focused on the treatment of large and giant wide-necked aneurysms between the petrous and cavernous segments of the ICA, for which the PED was approved originally. 4,6,24,37,40,46 These promising results led to increasing off-label use of the PED for aneurysms that are not large and not wide necked, and several groups have found similarly strong results after treating small aneurysms 11,17,26 and other off-label applications. 2,10,13,28,32,36 Still, the number of studies on use of the PED to treat small aneurysms has been limited, and very few have directly compared patient outcomes with those of patients after coiling or clipping.…”
Section: Discussionmentioning
confidence: 99%
“…2 Numerous studies have since demonstrated the safety and efficacy of the PED in treating aneurysms with varying morphologies in different anatomic locations. [3][4][5][6][7][8] As the clinical indications for PED placement expand, predictors of radiographic outcomes have become a topic of ongoing investigation. Although 1 study found that fusiform aneurysm morphology and shorter follow-up length were independent predictors of incomplete occlusion, this study was limited by a small sample size and a mean follow-up of 6.1 months.…”
mentioning
confidence: 99%
“…10 Numerous studies have since demonstrated the safety and efficacy of the PED in the treatment of aneurysms with varying morphologies and anatomic locations. [11][12][13][14][15][16] Currently, only a few studies with small numbers of patients have evaluated endovascular treatment of tandem aneurysms with coil embolization, 8 stentassisted coiling, 9 or flow diversion. 9 In this study, we compare the outcomes following deployment of a single PED in 2 groups of patients, those with solitary ICA aneurysms and those with tandem ICA aneurysms.…”
mentioning
confidence: 99%